A Nobel Affair : The Correspondence between Alfred Nobel and Sofie Hess - Nobel, Alfred Bernhard, 1833-1896 (Book collections on Project MUSE., 2017)
"Alfred Nobel made his name as an inventor and successful entrepreneur and left a legacy as a philanthropist and promoter of learning and social progress. The correspondence between Nobel and his Viennese mistress, Sofie Hess, shines a light on his private life and reveals a personality that differs significantly from his public image. The letters show him as a hypochondriac and workaholic and as a paranoid, jealous, and patriarchal lover. Indeed, the relationship between the aging Alfred Nobel and the carefree, spendthrift Sofie Hess will strike readers as dysfunctional and worthy of Freudian analysis. Erika Rummel's masterful translation and annotations reveal the value of the letters as commentary on 19th century social mores: the concept of honour and reputation, the life of a "kept" woman, the prevalence of antisemitism, the importance of spas as health resorts and entertainment centres, the position of single mothers, and more generally the material culture of a rich bourgeois gentleman. A Nobel Affair is the first translation into English of the complete correspondence between Alfred Nobel and Sofie Hess."--